Increasing Repurchase Intention through Product Quality and Pricing Strategy: A Fast-Food Sector Analysis - Suryani, Yosi; Miranda, Deva Dwi; Gustiawan, Willson (International Ecsis Association, 2024)
In today's competitive culinary market, repurchase intention serves as a key determinant of business profitability and sustainability. This study analyzes the impact of product quality and price on repurchase intention in the context of the fast-food sector,